Twenty‐five years of diabetes distress research. Issue 3 (31st October 2019) - Skinner, T. C.; Joensen, L.; Parkin, T.
Abstract: The term 'diabetes distress' first entered the psychosocial research vernacular in 1995, and refers to 'the negative emotional or affective experience resulting from the challenge of living with the demands of diabetes'. At first the proponents of the concept were hesitant in advocating that diabetes distress was a major barrier to individuals' self‐care and management of diabetes. Since then, a burgeoning body of evidence, now including several systematic reviews of intervention studies, suggests that diabetes distress, in both type 1 and type 2 diabetes, across ages and in all countries and cultures where it has been studied, is common and can be a barrier to optimal emotional well‐being, self‐care and management of diabetes. As a consequence, monitoring diabetes distress as part of routine clinical care is part of many national guidelines. The present narrative review summarizes this research and related literature, to postulate the aetiology of diabetes distress, and thus how it may be prevented. The current evidence base for the management of diabetes distress is summarized, and the next steps in the prevention and management of diabetes distress identified. What's new?: Diabetes distress is common among people with type 1 and type 2 diabetes, and is associated with lower levels of self‐care, general emotional well‐being and possibly metabolic outcomes of diabetes care. Whilst there has been a wealth of research on diabetes distress, we have limited data to show that distress is associated with the development of long‐term complications of diabetes, and we have little insight into how diabetes distress develops. There is emerging evidence that the way healthcare professionals communicate with people with diabetes may be exacerbating the distress experienced by people with diabetes, or possibly contributing to its development. Healthcare professionals need to ensure that the way they communicate with people who have diabetes does not add to the distress that diabetes engenders. We need to embed the assessment and management of diabetes distress into the routine diabetes care services we offer people with diabetes.